CYBERSECURITY TRENDS AND CHALLENGES: EMERGING THREATS, TECHNOLOGIES, AND STRATEGIES - Kalilaev Dauletiyar Bakhtiyarovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In our increasingly interconnected world, where digital transformation is accelerating across industries, cybersecurity stands as a critical pillar safeguarding sensitive data, infrastructure, and privacy. As technology evolves, so do the threats against it, necessitating continuous adaptation and innovation in cybersecurity strategies. This article explores the current landscape of cybersecurity, highlighting emerging threats, cutting-edge technologies, and effective strategies to mitigate risks.